Analysis of Burnout and Job Satisfaction with Intention to Leave among Indonesian Nurses in post Pandemic in Saudi Arabia - Nurul Uswatin; Yayi Suryo Prabandari; Agus Surono; Akhir Fahruddin (Universitas Muhammadiyah Surakarta, 2024)
The Covid pandemic has ended but health workers, especially nurses in Saudi Arabia, are still experiencing burnout due to high workloads. This study aims to analyze burnout and job satisfaction related to intention to leave among Indonesian nurses in health services in Saudi Arabia. This research used a qualitative method with a case-study approach. The research subjects used purposive sampling with a typical case of 12 Indonesian nurses who worked in health services and terminated their work contracts in Saudi Arabia. This research used data triangulation, source triangulation, and peer debriefing. In-depth interviews conducted at a predetermined place, data analysis follows 7 steps of Colaizzi's analysis. The results showed that burnout was closely related to emotional exhaustion, depersonalization, and low appreciation for one's abilities. Indonesian nurses who worked in health services in Saudi Arabia were happy and did not experience burnout. Meanwhile, job satisfaction or nurse satisfaction in dealing with work situations and environments is related to internal factors such as salary and rights to work facilities, while externally, it is related to self-development and professionalism.